CASE REPORT: PYOMETRA IN LOCAL CAT - Adnyana, I Made Agus; Gorda, I Wayan; Sudisma, I Gusti Ngurah (Buletin Veteriner Udayana, 2022)
Pyometra is a hormonal disorder that causes infection so that pus accumulates in the uterus, abscesses are usually caused by excess hormone progesterone, where the hormone progesterone causes thickening of the uterine wall. Pyometra is commonly found in dogs or cats, but is more common in dogs. A cat is 9 months old, weighs 1.95 kg and is female. Checked at the Animal Hospital, Faculty of Veterinary Medicine, Udayana University with complaints, the presence of runny out of animal genitals. The results of physical examinations that appear to come out of the animal's genitals, in the form of pus and stomach, look big like pregnant women. From hematological examination showed an increase in Hemoglobin 17.9 g / dL, reference values ??8.0 - 15.0 g / dL, and Mean Corpuscular Hemoglobin Concentration 41.4 g / dL reference values ??30.0 - 36.0 g / dL because animals lack oxygen so the hemoglobin level increases. Handling of Pyometra can be done by removing the uterus and ovary (ovariohysterectomy). Seven days postoperatively, the patient was declared cured and healthy again, with incisional wounds fused and no pus flowing out of the animal's genitals.